2010
DOI: 10.1248/bpb.33.683
|View full text |Cite
|
Sign up to set email alerts
|

Self-Dissolving Micropile Array Chip as Percutaneous Delivery System of Protein Drug

Abstract: Transdermal drug delivery systems (TDDS) have been challenged to increase the permeation rate of drugs through the skin and experimental strategies have included the use of chemical enhancers and physical methods. Of these, chemical enhancers have contributed most to the development of TDDS. Approximately 20 products of TDDS were launched on the US market by the end of 2008. Thus the penetration of small molecules through the skin can be enhanced by chemical enhancers.1) However, triggering of skin irritation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…Dissolving microneedles have been used to deliver EPO [121, 126], low molecular weight heparin [117], leuprolide acetate [123], desmopressin [122], and human growth hormone [122, 124, 201]. Coated microneedles have administered desmopressin [97], salmon calcitonin[202], and PTH (1-34) [89, 203204].…”
Section: Applications Of Microneedlesmentioning
confidence: 99%
“…Dissolving microneedles have been used to deliver EPO [121, 126], low molecular weight heparin [117], leuprolide acetate [123], desmopressin [122], and human growth hormone [122, 124, 201]. Coated microneedles have administered desmopressin [97], salmon calcitonin[202], and PTH (1-34) [89, 203204].…”
Section: Applications Of Microneedlesmentioning
confidence: 99%
“…An approximately 300 µm length from the top of dissolving microneedles was inserted into the skin, where dissolving microneedles encountered environmental water: Caspers et al reported that the water content in the skin was as high as 70% (44). In our previous report, pharmacokinetic evaluation of dissolving microneedles containing erythropoietin (EPO) was performed in rats and dogs, and species difference was studied (45). Higher BA of EPO was obtained in dogs, 65.9-69%, than in rats, 39.4%.…”
Section: Design Of Two-layered Dissolving Microneedlesmentioning
confidence: 99%
“…For example, protein denaturation during administration and/or subsequent storage process can result in limited therapeutic efficiency, altered regulatory response and impaired vaccination efficiency [5355]. Besides the maintenance of bioactivity, the therapeutic efficacy is also impacted by the drug absorption efficiency, which is determined by the chemical properties, the structural differences of the drug and the physiological conditions of the skin [56,57]. Cellular permeability related to the molecular size is also critical: proteins/peptides of less than approximately 5000 Da could transverse the skin layer and blood capillaries easily compared to those with the molecular weight greater than 20,000 Da [54,58,59].…”
Section: Types Of Delivered Proteinmentioning
confidence: 99%